PENGARUH MODEL PEMBELAJARAN ACTIVE LEARNING TERHADAP HASIL BELAJAR DI MTS AN NAHDLAH MAKASSAR - Eza, Muh Jabarullah; Syahid, Akhmad; Ahmad; Wahab, Abdul; A.Natsir, Andi Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of the Active Learning learning model on student learning outcomes in the subject of Islamic Cultural History at Madrasah Tsanawiyah An Nahdlah Makassar. This study uses a quantitative approach with an ex post facto research type. The study population was 240 seventh grade students, while the research sample was 71 students determined using the Simple Random Sampling technique with the Slovin formula. Data collection techniques were carried out through observation, interviews, questionnaires, and documentation. The research instrument has been tested for validity and reliability, while data analysis used descriptive analysis, classical assumption tests, multiple linear regression analysis, partial tests (t tests), simultaneous tests (F tests), and coefficient of determination (R²) tests with the help of the SPSS program. The results showed that partially the Preparation stage (X1) had a significant effect on learning outcomes with a calculated t value of 3.632 and a significance of 0.001 <0.05. The Orientation and Motivation variable (X2) also has a significant effect with a t-value of 6.082 and a significance of 0.000 <0.05, while the Reflection and Evaluation variable (X3) shows a significant effect with a significance of 0.000 <0.05. Simultaneously, the Active Learning learning model has a significant effect on learning outcomes with a calculated F value of 25.366> F table 2.788 and a significance of 0.000 <0.05. The coefficient of determination (R²) value of 0.817 indicates that 81.7% of the variation in learning outcomes is influenced by the Active Learning learning model, while 18.3% is influenced by other factors outside the study. The Reflection and Evaluation variable provides the most dominant contribution to learning outcomes. Thus, the application of the Active Learning learning model has proven effective in improving student learning outcomes in the subject of Islamic Cultural History at Madrasah Tsanawiyah An Nahdlah Makassar.